Penerapan Rekam Medis Elektronik dalam Menunjang Efektivitas Kerja Perekam Medis di Rumah Sakit Hasna Medika Cirebon - Tasbihah, Firyal; Yunengsih, Yuyun (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This study aims to analyze the impact of implementing electronic medical records (RME) in enhancing the effectiveness of medical recorders' work at Hasna Medika Hospital, Cirebon. The qualitative method was employed, with data collection techniques including observation, interviews, and literature review. The results indicate that the implementation of RME at Hasna Medika Hospital, Cirebon, is sufficiently effective in terms of security, data integrity, and availability. Additionally, RME has reduced the workload for medical recorders and accelerated the medical recording process. However, challenges such as server disruptions and discrepancies between service indicator outputs and manual calculations were identified. To address these issues, the hospital needs to refine the RME system according to user requirements to further enhance the effectiveness of medical recorders.